Uso de drones como herramienta tecnológica para la detección de plagas y malezas, en los cultivos de arroz de la finca Carimata. (2021)
The objective of the following thesis is to determine the feasibility of drones in the detection of plagues and weeds in rice crops at the Caritama farm. It has been made a case investigation with descriptive scope, as first step it was made an actual study state about the investigated farm in case of the activities about the detection of plagues and weed at the rice crops, In which one it was determinated that currently the farm realize the detection activities in a manual way, causing loss in time at the gross inspection. It was established the method by which it is grounded the activities about the technological tool use and work phases, and finally the realization of a benefit-cost analysis in a qualitative form that determine the most favorability method in plagues and weeds detection.